Authority of Forestry Police in the Completion Process of Forest Occupation Criminal Acts Cases: Between Expectation and Reality - Lukitasari, Diana; Shofwan, Anieq Nisrina (Universitas Negeri Semarang, 2019)
This research is intended to determine the authority possessed by the forestry police related to the crime of forest occupation and how far the implementation of the authority in the process of settling the case of the crime of forest occupation. This research is an empirical law study, by conducting interviews, direct observation, and literature study. The problem of forest occupation in the area of Alas Purwo National Park is a long-standing problem that can not be solved sooner which can lead to reduced protected areas and disrupt natural ecosystems that already exist around the site of the forest occupation. The existence of citizens who have been found guilty by the court violated Article 78 paragraph (2) jo. Article 50 paragraph 3 sub-paragraph of Law Number 41 of 1999 on Forestry jo. Article 55 paragraph (1) of the Criminal Code (KUHP) related to illegal criminal acts of forest occupation but until this day they still occupy the jungle zone of Alas Purwo National Park area also can disrupt the duties of the forestry police in its efforts to secure the forest. Besides due to the lack of public awareness of the importance of forest existence, the settlement process of forest occupation is also constrained by internal factors of forestry police, namely the understanding of the forestry police on the extent of their authority.